TRANSFORMASI INSTRUMEN PEMBIAYAAN AKAD MURABAHAH BIL WAKALAH MENURUT FATWA DEWAN SYARIAH NASIONAL DAN PENERAPANNYA DI BANK SYARIAH MANDIRI KCP BARABAI KABUPATEN HULU SUNGAI TENGAH - Muhammad Iqbal Sanjaya (Institut Agama Islam Darul Ulum Kandangan, 2020)
This research was born based on the author's academic anxiety in seeing the application of financing applications based on the murabahah contract instrument at Bank Syariah Mandiri KCP Barabai that has not complied with the guidelines or fatwas of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). The purpose of this research is to comprehensively see the suitability of regulations or fatwas with the level of application. This research is an empirical juridical research which means research that departs from a regulatory perspective and looks from the implementation side in the field. Data collection techniques using observation and interview methods. The results of this study are based on the author's formulation, first: Regulation or Fatwa DSN-MUI as the operational validity of the financing instrument with a murabahah agreement totaling 12 (twelve) fatwas with details of 11 (eleven) fatwas on murabahah and 1 (one) fatwa regarding wakalah as a supporting fatwa in the smooth process of murabahah financing, because the distribution of funds based on the murabahah contract at BSM KCP Barabai cannot be carried out with a single contract (murabahah) so it requires a supporting contract, namely wakalah, therefore murabahah bil wakalah is said. Second: The murabahah loan application for Bank Syariah Mandiri KCP Barabai is still not in accordance with the National Sharia Council (DSN) fatwa number 04/DSN-MUI/IV/2000 regarding Murabahah in the general provisions in point (h), and is also not in accordance with the Standard Book Sharia Banking Products as guidelines for implementing murabahah operations. Because the object in murabahah does not exist, it is only limited to the formality stated in the financing clause.